Research progress on the relationship between mitochondrial function and heart failure: A bibliometric study from 2002 to 2021 - Qi, Xiang; Zhu, Zhide; Wang, Yuhan; Wen, Zhihao; Jiang, Zhixiong; Zhang, Liren; Pang, Yan; Lu, Jianqi (Frontiers in Molecular Biosciences, 2022)
Heart failure is one of the major public health problems in the world. In recent years, more and more attention has been paid to the relationship between heart failure and mitochondrial function. In the past two decades, a growing number of research papers in this field have been published. This study conducted a bibliometric analysis of the published literature on the relationship between MF and HF in the past 20 years by utilizing Microsoft Excel 2019, Biblio metric analysis platform, WoSCC database, VosViewer and Citespace. The results show that the papers have increased year by year and China and the United States are the leading countries in this field, as well as the countries with the most cooperation and exchanges. UNIVERSITY OF CALIFORNIA SYSTEM is the research institution with the greatest impacts on research results, and Yip H.K. is the author with more papers. The American Journal of Physiology-heart and Circulatory Physiology is probably the most popular magazine. At present, most of the published articles on mitochondria and HF are cited from internationally influential journals. The research focus includes oxidative stress, metabolic dysfunction, mitochondrial Ca2+homeostasis imbalance, mitochondrial quality control and mitochondrial dysfunction mediated by inflammation in the pathogenesis of HF. Targeted regulating of mitochondria will be the keynote of future research on prevention and treatment of HF.